West African Economic and Monetary Union : Staff Report on Common Policies for Member Countries-Press Release; Staff Report; and Statement by the Executive Director for the West African Economic and Monetary Union. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
After almost a decade of strong growth, the WAEMU region is facing severe challenges from a triple crisis impacting the health, economic and security situations. Both fiscal and monetary policies were relaxed significantly in 2020 to contain the pandemic and support the economy. A gradual fiscal consolidation is expected to start in 2021 and bring back the aggregate fiscal deficit towards the 3 percent of GDP regional ceiling within three years. Growth is expected to recover swiftly in 2021-22 to pre-crisis levels, but the economic outlook is still uncertain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet